The Validity and Reliability of the Thanatophobia Scale-Turkish Form: a Psychometric Study Among Nurses - Cifcioglu, Zulfiye Yildiz; Seren, Arzu K. Harmanci; Yildiz Çifçioğlu, Zülfiye; Harmanci Seren, Arzu K. (Sage Publications inc, 2024)
Purpose: To examine the validity and reliability of the Thanatophobia Scale-Turkish Form among nurses. Design and methods: This methodological study included 154 nurses. Content and construct validity, item analysis, confirmatory factor analysis, and internal consistency were used to evaluate the data. Findings: The content validity index of the scale was 0.91. Item-total score correlation values varied between 0.453 and 0.718. As a result of the confirmatory factor analyses, one factor was confirmed. Cronbach's alpha internal consistency coefficient was 0.854. Practice Implications: Thanatophobia Scale-Turkish Form is a valid and reliable tool used to evaluate the fear of death among nurses.
Keywords: Thanatophobia; Fear Of Death; Nursing; Validity; Reliability